2022
DOI: 10.1093/eurheartj/ehac339
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis in homozygous familial hypercholesterolaemia: a paradigm shift over a century

Abstract: Aims Homozygous familial hypercholesterolaemia (HoFH) is an orphan disease defined by extreme elevations in low-density lipoprotein cholesterol, cutaneous xanthomas, and pre-mature atherosclerotic cardiovascular disease. Survival has more than doubled over the past three decades. Aortic stenosis (AS) [supravalvular aortic stenosis (SVAS) or valvular aortic stenosis (VAS)] is commonly encountered. There are no medical treatments available and complex high-risk surgeries represent the only avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…17 Secondly, it has been shown that FH is associated with some of the valvular diseases, especially with aortic valve stenosis. 18,19 Recent Mendelian randomization studies have suggested that LDL cholesterol as well as lipoprotein (a) [Lp(a)] both of which are elevated in patients with FH appear to be causally associated with developing aortic valve stenosis. 20 Thus, FH status may lead to increased HF and AF via increased risk for valvular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Secondly, it has been shown that FH is associated with some of the valvular diseases, especially with aortic valve stenosis. 18,19 Recent Mendelian randomization studies have suggested that LDL cholesterol as well as lipoprotein (a) [Lp(a)] both of which are elevated in patients with FH appear to be causally associated with developing aortic valve stenosis. 20 Thus, FH status may lead to increased HF and AF via increased risk for valvular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is reasonable to think that one of the major causes of HF and AF is ASCVD, and thus FH is associated with HF and AF because FH is strongly associated with ASCVD 17 . Secondly, it has been shown that FH is associated with some of the valvular diseases, especially with aortic valve stenosis 18,19 . Recent Mendelian randomization studies have suggested that LDL cholesterol as well as lipoprotein (a) [Lp(a)] both of which are elevated in patients with FH appear to be causally associated with developing aortic valve stenosis 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Inclisiran, a small interfering RNA that inhibits hepatic synthesis of PCSK9, is being evaluated in ASCVD outcome trials (NCT03705234, NCT05030428) but not in the prevention of AS [56]. The impact of lipoprotein apheresis on CAVD is unclear; current data are limited to observational studies of individuals with homozygous FH [48].…”
Section: Lipoprotein(a)-lowering and Prevention Of Aortic Stenosismentioning
confidence: 99%
“…Initial efforts at preventing AS focused on reducing atherogenic lipoproteins, particularly LDL-cholesterol [47]. Additionally, individuals with homozygous FH have a high prevalence of supravalvular and valvular AS [48,49]. However, statins have not been demonstrated to slow the progression of AS [10 ▪ ,13].…”
Section: Reviewmentioning
confidence: 99%
“…46 AS is mainly evaluated by echocardiography, and seldom by invasive cardiac catheterization, contrast angiography or cardiac magnetic resonance imaging (MRI). 53, 54 Presence of (non-) calcified plaques, perivascular inflammation and hemodynamic obstructive lesions can be evaluated by prospective ECG-triggered CT coronary angiography (CTCA). Potential ischemia due to obstructive coronary artery stenoses should be primarily evaluated by non-invasive functional tests, such as exercise ECG, stress perfusion with PET-CT, cardiac MRI or Single Photon Emission CT Myocardial Perfusion (SPECT).…”
Section: Consensus Statementsmentioning
confidence: 99%